2012
DOI: 10.1007/s10714-012-1331-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical instability and the expansion-free condition

Abstract: We study the dynamical instability of a spherically symmetric anisotropic fluid which collapses adiabatically under the condition of vanishing expansion scalar. The Newtonian and post Newtonian regimes are considered in detail. It is shown that within those two approximations the adiabatic index $\Gamma_1$, measuring the fluid stiffness, does not play any role. Instead, the range of instability is determined by the anisotropy of the fluid pressures and the radial profile of the energy density, independently of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(100 citation statements)
references
References 39 publications
3
97
0
Order By: Relevance
“…The Santos junction conditions have been generalised to include shear [5,6], the cosmological constant as well as the electromagnetic field [7,8]. Since 1985 there has been a concerted effort in generating exact models of dissipative collapse with Herrera and co-workers establishing many of the fundamental results in terms of stability, energy conditions and thermodynamics of these models [9][10][11][12][13][14]. Maartens et al investigated the temperature and luminosity profiles of these models by employing casual thermodynamics [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The Santos junction conditions have been generalised to include shear [5,6], the cosmological constant as well as the electromagnetic field [7,8]. Since 1985 there has been a concerted effort in generating exact models of dissipative collapse with Herrera and co-workers establishing many of the fundamental results in terms of stability, energy conditions and thermodynamics of these models [9][10][11][12][13][14]. Maartens et al investigated the temperature and luminosity profiles of these models by employing casual thermodynamics [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated by Chandrasekhar [17] and Herrera et al [18] that all the terms coming in the stability conditions should be positive definite. Therefore, to attain the instability regions of the cylindrical stellar system, we consider each term in the respective collapse equation to be positive.…”
Section: N Approximationsmentioning
confidence: 98%
“…Initially, the celestial system is considered to be in hydrostatic equilibrium, but as time passes, it is subject to oscillatory motion. All the metric functions and fluid parameters can be perturbed [18],…”
Section: Perturbation Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Horvat et al [24] explored that instability of anisotropic star occurs at higher surface compactness when the anisotropy of the pressure is present. Herrera et al [25] discussed the dynamical instability of expansionfree fluid at Newtonian and post Newtonian order and found that the range of instability is determined by the anisotropic pressure and radial profile of the energy density. In a recent paper [26], this problem has been explored in f (R) gravity.…”
Section: Introductionmentioning
confidence: 99%